Eating attitudes and depressive symptoms in a LGBTIQ sample in Turkey - Gulec, Hayriye; Torun, Tayfun; Prado, Aneliana da Silva; Bauer, Stephanie; Rummel-Kluge, Christine; Kohls, Elisabeth (Frontiers in Psychiatry, 2022)
Background: Lesbian, gay, bisexual, transgender, intersexual and queer (LGBTIQ) individuals are often stigmatized due to their minority status. Sexual-minority stress is often discussed as a risk factor for the increased mental health problems reported in this population. Objective: The current study (1) investigated eating attitudes and depressive symptoms in a sexual minority sample from Turkey who identify themselves as LGBTIQ and (2) explored the role of sexual minority stressors beyond the potential predictors of eating attitudes and depressive symptoms in this population. Methods: Recruitment was supported and streamlined by several Turkish NGOs and LGBTIQ community networks. Sociodemographic measures, eating attitudes, depressive symptoms, sexual minority stressors (e.g., heterosexist experiences, internalized homophobia), and the potential predictors of eating attitudes and depressive symptoms were assessed with an anonymous online survey between February 2022 and June 2022. The sample consisted of 440 participants. The mean age was 31.92 (SD = 11.82). The majority of the participants reported their current gender identity as male (64.3%; n = 440) and their sexual orientation as attracted to men (62.8%; n = 439). For 79.7% of the participants, the assigned sex at birth was man (n = 439). Results: Two separate three-stage multiple hierarchical regression analyses were conducted, controlling for sociodemographic characteristics and the risk and protective factors of eating attitudes and depressive symptoms. Disturbed eating attitudes were predicted by assigned female sex at birth, higher scores for depression, social isolation, and the total number of heterosexist experiences, and lower distress related to heterosexist experiences. Depressive symptoms were predicted by assigned female sex at birth, lesbian sexual orientation, disturbance in eating attitudes, increases in generalized anxiety, and distress related to daily heterosexist experiences. Conclusion: The current study demonstrated the significant role of sexual minority stressors in the prediction of disturbed eating attitudes and depressive symptomatology beyond the general psychosocial vulnerability factors. These findings emphasize the need for developing strategies to reduce prejudicial attitudes at the societal level and to enhance the skills of LGBTIQ individuals in coping with sexual minority stressors in Turkey.